2019
DOI: 10.3389/fpsyg.2019.00688
|View full text |Cite
|
Sign up to set email alerts
|

Endorsing and Reinforcing Gender and Age Stereotypes: The Negative Effect on Self-Rated Leadership Potential for Women and Older Workers

Abstract: Previous research has examined the impact of stereotypes on outcomes such as career progression and hiring decisions. We present a novel approach to examine the role of stereotypes in predicting self-rated leadership potential across gender and age groups. This research sheds light on the impact of leadership-incongruent and detrimental stereotypes about one's gender and age, for women and older workers, on self-ratings of leadership potential. Across three studies (total N = 640), corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…Moreover, members of the groups for which negative stereotypes exist adjust their own behaviour when confronted with self-group prejudices and/or feel the need for acting in conformity with the stereotypes about the group, resulting in self-fulfilling prophesies, where in-group members consciously or unconsciously adjust their behaviour to the stereotype (Steele and Aronson 1995;Hilton and von Hippel 1996). This can lead to lower levels of performance in a professional context (Steele and Aronson 1995;Kunda and Thagard 1996;Eckes 2002;Tresh et al 2019).…”
Section: Professional Stereotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, members of the groups for which negative stereotypes exist adjust their own behaviour when confronted with self-group prejudices and/or feel the need for acting in conformity with the stereotypes about the group, resulting in self-fulfilling prophesies, where in-group members consciously or unconsciously adjust their behaviour to the stereotype (Steele and Aronson 1995;Hilton and von Hippel 1996). This can lead to lower levels of performance in a professional context (Steele and Aronson 1995;Kunda and Thagard 1996;Eckes 2002;Tresh et al 2019).…”
Section: Professional Stereotypesmentioning
confidence: 99%
“…These cognitive schemes are at the basis of processing information about actual people, and in turn influence decisions on how to behave in relation to these people (Bodenhausen 1990; Kunda and Thagard 1996). As a result, stereotypes have been dealt with from various perspectives in various areas of social sciences, focusing on gender, race, nationalities and/or age groups (Steele and Aronson 1995;Eckes 2002;Ellemers 2018;Tresh et al 2019). Also, in the literature on professional image and individual reputations, stereotypes are conceptualized and analysed to better understand human interactions among and with employees, subordinates, leaders, customers and citizens (Vigoda 2000;Roberts 2005;Uhlmann et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the selective activation of individual categories, research has demonstrated the relevance of considering the simultaneous activation of multiple categories. For instance, when both age and gender information is present, both interact to inform judgments about others and even the self (Ramos et al, 2016;Sng et al, 2019; specifically in a work place context: Duncan & Loretto, 2004;Tresh et al, 2019). Furthermore, stereotypes often overlap across multiple categories (e.g., Galinsky et al, 2013), which means that a certain trait, behavior, or characteristic may be typical of several different categories.…”
Section: Discussionmentioning
confidence: 99%
“…We defer a thorough definition, complete with mathematical formalization, to Definition 3.8. In societal systems, GSR is measured by the agreement of human constituents with gender stereotype descriptors [69,80]. In operationalizing this construct, we aim to quantify the impact of SEs on the perception of gender: more specifically, its alignment to existing direct and indirect stereotypes encoded in culture and language.…”
Section: Definition 32 Gender Stereotypementioning
confidence: 99%